2017
DOI: 10.1371/journal.pone.0184847
|View full text |Cite
|
Sign up to set email alerts
|

A one-year prospective study of colonization with antimicrobial-resistant organisms on admission to a Vietnamese intensive care unit

Abstract: There is a paucity of data regarding initial bacterial colonization on admission to Intensive Care Units (ICUs) in low and middle-income countries (LMICs). Patients admitted to ICUs in LMICs are at high-risk of subsequent infection with antimicrobial-resistant organisms (AROs). We conducted a prospective, observational study at the Hospital for Tropical Diseases in Ho Chi Minh City, Vietnam from November 2014 to January 2016 to assess the colonization and antimicrobial susceptibility of Staphylococcus aureus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…coli , Klebsiella spp., Pseudomonas spp. and Acinetobacter spp.. Staphylococcal colonies were checked for catalase and coagulase, plus checked for methicillin resistance using cefoxitin disc diffusion, and re-checked on the matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDITOF, Bruker) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli , Klebsiella spp., Pseudomonas spp. and Acinetobacter spp.. Staphylococcal colonies were checked for catalase and coagulase, plus checked for methicillin resistance using cefoxitin disc diffusion, and re-checked on the matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDITOF, Bruker) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In LMICs, such as Vietnam, there is a large amount of antimicrobial use in the community [ 12 , 13 ]. In our previous publication, we found that up to 63.1% (529/838) patients colonized with AROs on ICU admission [ 14 ]. Due to a paucity of antimicrobial stewardship programs, the situation of colonization, infection and antimicrobial resistance may be different and more serious in our country.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a secondary analysis of 9 data sets: 8 cohort studies (5 prospective and 3 retrospective) and 1 randomized clinical trial. [8][9][10][11][12][13][14][15] Of the countries represented in this study (Bangladesh, Haiti, India, Indonesia, Myanmar, Rwanda, Sierra Leone, Sri Lanka, Thailand, and Vietnam), 3 are classified as low income, 6 as lower middle income, and 1 as upper middle income by the World Bank. 16 Patients were recruited to the cohorts from a range of hospital settings, including small community hospitals, military hospitals, rural regional hospitals, national referral hospitals, and specialty infectious disease hospitals.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…Recent study in Taiwan, found just 0.2% of A . baumannii intestinal carriage from ICU admitted patients [18]. Furthermore, mouth/throat, skin and rectal swabs samples in a Turkish ICU revealed that 6.3% of adults hospitalised were colonized by A .…”
Section: Discussionmentioning
confidence: 99%